A Cross‐Coupling Reaction Between Aliphatic Aldehydes And Sulfonium Salts. Issue 1 (11th October 2021) - Chen, Baoli; Li, Li; Chen, Jiean; Huang, Yong
Abstract: The synthesis of multi‐substituted electron‐deficient alkenes is often accomplished via cross‐coupling of diazo compounds in the presence of a metal catalyst. Herein, we report an organocatalytic protocol that enables the direct coupling of aliphatic aldehydes with sulfonium ylides. A key carbene mimetic, α‐iodoenamine/enol, is believed to engage in direct cross‐coupling with a sulfonium ylide, delivering α, β‐unsaturated carbonyl compounds with a formyl substituent. The reaction demonstrated remarkably mild conditions, convergence, and control of olefin geometry. Abstract :